OPOSISI MAKNA DALAM BAHASA LIO - Ni Made Suryati (Fakultas Sastra Universitas Negeri Malang, 2015)
This study is aimed to describe and explain (1) the types of the use of antonym in Lionese; (2) the categories of Lionese antonyms; and (3) units of language that may be in opposition of meaning in Lionese. The cornerstone of the theory used is the semantic theory, especially the antonym word-meaning relation. Data collected by the method see face to face with the record and recording techniques. , The results showed as follows. First, the kind of opposition Lio meaning there are five, namely (a) the absolute opposition, (b) polar opposites, (c) opposition relations, (d) hierarchical opposition, and (e) the opposition compound. Second, the category of vocabulary Lio to opposing meanings are (a) nouns, (b) pronouns, (c) numeralia, (d) of the verb, and (e) adjective. Third, the forms to the opposition in a Lio is (a) forms the basis of the basic form, (b) basic shape with the shape prefixed, (c) forms prefixed with the form prefixed, (d) the basic form with a group of words, and ( e) a group of words with a group of words.